Role of Women Entrepreneurship in Economic Development of Nepal - Khatri Basnet, Rati (Cognition, 2024)
The study tells that women entrepreneurs play a vital role not only in the development of industrial sector of a country but also in the development of farm and service sector. The role of women entrepreneurship in economic development varies from economy to economy depending upon its material resources, industrial climate and the responsiveness of the political system to the entrepreneurial function. The objective of the study is to find out the role of women entrepreneurship in economic development of our country. The study is based on secondary data and analytical approach. Women entrepreneurs, in the form of new goods & services, result in new employment, which can produce a cascading effect or virtuous circle in the economy. It is necessary that we understand the benefits of women entrepreneurs, a balanced approach to nurturing entrepreneurship will definitely result in a positive impact on economy and society.